1995
DOI: 10.1073/pnas.92.22.10422
|View full text |Cite
|
Sign up to set email alerts
|

Relating aromatic hydrocarbon-induced DNA adducts and c-H-ras mutations in mouse skin papillomas: the role of apurinic sites.

Abstract: Mouse skin tumors contain activated c-H-ras oncogenes, often caused by point mutations at codons 12 and 13 in exon 1 and codons 59 and 61 in exon 2. Mutagenesis by the noncoding apurinic sites can produce G -* T and A --T transversions by DNA misreplication with more frequent insertion of deoxyadenosine opposite the apurinic site. Papillomas were induced in mouse skin by several aromatic hydrocarbons, and mutations in the c-H-ras gene were determined to elucidate the relationship among DNA adducts, apurinic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
208
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(217 citation statements)
references
References 44 publications
8
208
0
1
Order By: Relevance
“…CSC, B[a]P, and other constituents of CSC have been shown to generate abasic DNA damage in cells (Chakravarti et al, 1995;DeMarini et al, 1995;Cavlieri and Rogan, 1998). However, the mechanism by which they are repaired is not yet well described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CSC, B[a]P, and other constituents of CSC have been shown to generate abasic DNA damage in cells (Chakravarti et al, 1995;DeMarini et al, 1995;Cavlieri and Rogan, 1998). However, the mechanism by which they are repaired is not yet well described.…”
Section: Discussionmentioning
confidence: 99%
“…Those adducts that are repaired by the BER pathway, can be either stable or depurinating. Through comprehensive studies of the DNA adducts of B[a]P, Cavalieri and Rogan (1998) and Chakravarti et al (1995) have demonstrated a strong association between depurinating adducts and oncogenic mutations in the H-ras gene, suggesting that these adducts are important in tumor initiation and progression. Furthermore, it has been found that in lung cancer cells, approximately 30% of GC to TA transversions occur at the hot spot codon 248 and 273 of TP53 gene and at codon 12, 13 or 61 of K-ras gene (Slebos et al, 1991;Husgafvel-Pursiainen et al, 1993;Westra et al, 1993;Greenblatt et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH are ubiquitous environmental contaminants that result from incomplete combustion processes and are known carcinogens [8]. PAH are thought to exert their carcinogenic properties through their ability to form PAH-DNA adducts [9][10][11]. Both casecontrol [12] and cohort [13] studies have found that most jobs associated with occupational PAH exposure have the potential for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the BP radical cation can yield N7 and C8 depurinating adducts with guanine and adenine that have resulted in H-ras mutation in mouse skin (9,10). (±)-Anti-BP-7,8-diol-9,10-epoxide a representative diol-epoxide can form stable N 2 -adducts with 2′-deoxyguanosine in vivo and in vitro (11)(12)(13)(14) and leads to the mutation of p53 and H-ras (3,15).…”
Section: The Three Classes Of Reactive Pah Metabolites (Radical Catiomentioning
confidence: 99%